Comparison of modified Schirmer's test and clinical oral dryness score scale in the clinical assessment of oral dryness in postmenopausal women - P Roland Prethipa; Jimsha Vannathan Kumaran; Srinivasan Subramanian Vasudevan; Mariappan Jonathan Daniel (Wolters Kluwer Medknow Publications, 2019)
Aims: The aim of this study was to assess the oral dryness in postmenopausal women and to correlate the salivary flow rate determined by modified Schirmer's test (MST) with the clinical oral dryness score (CODS) obtained from Challacombe Scale. Subjects and Methods: Forty postmenopausal women were questioned regarding their oral dryness status. Patients complaining of xerostomia formed the case group and rest formed the control group. CODS was assessed based on the ten features of oral dryness. Unstimulated whole salivary flow rate was assessed by MST. Statistical Analysis Used: All data were analyzed using inferential statistics such as Chi-square, Fisher's exact test, and Spearman correlation, and the analysis was carried out with SPSS 17. Results: There was statistically significant difference between case and control group with regard to CODS (P = 0.001) and modified Schirmer's (P = 0.004). A low-negative correlation was observed between modified Schirmer's score and CODS (r = -0.17). Conclusion: Since CODS correlated with modified Schirmer's score, it indicates that CODS can be utilized for semiquantitative assessment of oral dryness.